State insurance and mother's pensions - Dickie, Alfred (Statistical and Social Inquiry Society of Ireland, 1919)
Mr. President, Ladies and Gentlemen, the subject that I wish to bring before you this evening is one of great interest to the public in general, and especially to a Society like this. From the statistics supplied from your department, Mr. President, it appears that for the last quarter the deaths have exceeded the births by a considerable amount. If this continues it will be disastrous to the country. Now, we may not be able to increase the birth-rate, as that depends on economic and other causes which we cannot by any action on our part effect. But we can and ought to take all possible measures to ensure that every child born into this world has a proper chance of growing up and growing into an efficient citizen.
Read April 14th, 1919
Keywords: Social insurance; Child welfare; 314.15